Pengaruh Terapi Tertawa Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Ringan di Desa Ranjiwetan Majalengka - Velindria, Kiki Meliza; Badriah, Dewi Laelatul; Ramadhy, Asep Sufyan (Sekolah Tinggi Ilmu Kesehatan Kuningan, 2012)
Introduction: Hypertension is one of public health problem that requires a good handling because of its prevalence is quite high. The prevalence of hypertension in Indonesia reached 31.7% of the population at the age of 18 years and over. Of that amount, 60% ended in stroke patients with hypertension. Lifestyle modification is one alternative therapy, including laughter therapy. This study aims to examine the effect of laughter therapy to decrease blood pressure in hypertensive patients in Puskesmas Kasokandel Majalengka. Method: This study is designed by quasi-experimental research design with pre-test and post-test control group design. The subject consist 48 people who meet the inclusion criteria. Research subjects were divided into 2 groups: 24 persons as the treatment group and 24 others as the control group. The research data is analyzed by MANAVA test (multivariate analysis) using the least significance difference. Results: The results showed there were highly significant differences (p=0,000) between the average systolic blood pressure/diastolic in the group treated with the control group. Likewise there is a very significant difference (p=0,000) on average systolic blood pressure/diastolic between the various treatment groups to-1 to treatment to-6 with a maximum of 11 mm Hg reduction in systolic pressure and 14.8 mm Hg in diastolic pressure. Discussion: Nurses can promote laughter therapy as part of lifestyle modification or non-pharmacologic therapy for patients with hypertension, especially patients with mild hypertension and may consider laughing become a therapy remains one of the procedures in the management of mild hypertension in the health center.